2019
DOI: 10.3892/ol.2019.11020
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine‑induced killer cells/natural killer cells combined with anti‑GD2 monoclonal antibody increase cell death rate in neuroblastoma SK‑N‑SH cells

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International (CC BY-NC-ND 4.0) License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…These findings Dinutuximab in combination with activated NK cells targets GD2 + cells via ADCC Treatment with dinutuximab in combination with NK cells has produced promising outcomes in preclinical studies of neuroblastoma. 30 To determine whether NK cells enhance the efficacy of dinutuximab against GD2 + breast cancer cells, we treated SUM159 cells with dinutuximab or rituximab (20 μg/mL) alone or in combination with IL-21-activated human peripheral blood-derived NK cells (online supplemental figure 7) at a different target:NK-cell ratios. We then determined the percentage of GD2 + SUM159 cells using flow cytometry.…”
Section: Open Accessmentioning
confidence: 99%
“…These findings Dinutuximab in combination with activated NK cells targets GD2 + cells via ADCC Treatment with dinutuximab in combination with NK cells has produced promising outcomes in preclinical studies of neuroblastoma. 30 To determine whether NK cells enhance the efficacy of dinutuximab against GD2 + breast cancer cells, we treated SUM159 cells with dinutuximab or rituximab (20 μg/mL) alone or in combination with IL-21-activated human peripheral blood-derived NK cells (online supplemental figure 7) at a different target:NK-cell ratios. We then determined the percentage of GD2 + SUM159 cells using flow cytometry.…”
Section: Open Accessmentioning
confidence: 99%
“…A study by Agarwal et al found G-CSF to be a "tumorigenic growth factor for neuroblastoma" by promoting the expansion of cancer stem cell-like subpopulations in vitro and in vivo, and the authors suggested "a comprehensive re-evaluation of the clinical use of G-CSF in these patients" (88). Zhang et al determined that either anti-GD2 mAb or cytokine-induced killer (CIK)/NK cells isolated from cord blood mononuclear cells significantly provoked apoptosis of neuroblastoma cell line SK-N-SH compared with controls, as assessed by flow cytometry (89). The authors also showed that anti-GD2 mAb and CIK/NK cells in combination significantly increased apoptosis compared with either treatment separately in vitro.…”
Section: Neuroblastomamentioning
confidence: 99%
“…Zhang et al determined that either anti-GD2 mAb or cytokine-induced killer (CIK)/NK cells isolated from cord blood mononuclear cells significantly provoked apoptosis of neuroblastoma cell line SK-N-SH compared with controls, as assessed by flow cytometry ( 89 ). The authors also showed that anti-GD2 mAb and CIK/NK cells in combination significantly increased apoptosis compared with either treatment separately in vitro .…”
Section: Targeting Disialoganglioside Gd2-expressing Tumorsmentioning
confidence: 99%
“…17 Based on these characteristics of GD2, a number of GD2specific immunotherapy strategies have been developed, including specific antibodies, drug coupling and chimeric antigen receptor-modified T cell therapy. 13,14,[18][19][20][21] Although the introduction of anti-GD2 monoclonal antibodies can temporarily improve the survival of neuroblastoma patients, approximately 50% of them will eventually relapse and die. 7 These patients need more effective and targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…17 Based on these characteristics of GD2, a number of GD2-specific immunotherapy strategies have been developed, including specific antibodies, drug coupling and chimeric antigen receptor-modified T cell therapy. 13,14,18 21…”
Section: Introductionmentioning
confidence: 99%